A insuficiência das justificações do Estado moderno: contratualismo e procedimentalismo na inflexão da modernidade - Gamba, João Roberto Gorini (2018)
This thesis works with the concept of justification of the State, differentiating it from the legitimacy (empirical aspect) and legality (normative aspect) and seeks to verify the fulfillment of the justifying function of contractarianism and proceduralism models in the context of modernity and late modernity, respectively. To do that, it uses a historical-evolutionary approach to the problem of justification. Therefore, it verifies the insufficiency of contractarianism and proceduralism justifications, but not without first realizing a historical reconstruction of the problem, presenting the Aristotelian theory in antiquity, and the theological-religious, typical of the Middle Age, noting the need for a rationally structured justification for the political and legal order in modernity. In this context, contractarianism theories will be presented to fulfill this function and are analyzed here from their different formulations, from Thomas Hobbes to Immanuel Kant, through John Locke and Jean-Jacques Rousseau, verifying the importance of these theories for the configuration of Modern state. Then, it analyzes the overlapping consensus by John Rawls, the legitimation by procedure by Niklas Luhmann, and procedural theory of deliberative democracy by Jürgen Habermas, as they contribute to the problem of State justification and seek to give additional breath to the modern project. In the end, it concludes by the insufficiency of contractarianism and proceduralism models in their task of justifying the Modern State, which undermines the effectiveness of its legal system, especially with the advent of late capitalism, in which the problem of justification is aggravated by the advance of science and technique not only in productive models, but especially in politics with the denominated technocracy, in such a way as to affect the founding constructs of modernity, notably by reducing the participation of the individual in the productive system and in the democratic process, forcing us to rethink the typically modern forms of State and law in a moment of a possible inflection of modernity